The Influences of Social Media and Scientific Citation in Hasanuddin University and Halu Oleo University: An Altmetric Approach - Nurul Azizah; Cecep Ibrahim; Asrul Jaya (Program Studi Ilmu Perpustakaan UIN Alauddin, 2022)
Altmetrics is a statistical measuring tool to measure interactions in scientific articles through data obtained from social media. This research examines the effect of social media data on citation data of scientific papers from Hasanuddin University and Halu Oleo University. This research uses quantitative descriptive with correlational analysis method. The stages of this research consist of problem identification, data collection, data pre-processing, analysis of the altmetrics approach, and discussion results. This research was conducted online by retrieving data in the form of citation data of scientific papers entering keywords with affiliates of Hasanuddin University and Halu Oleo University and the year was limited from 2019-2021, while social media data was obtained from Altmetrics.com by extracting DOIs from every scientific publication on Scopus. The results of this study indicate the correlation test results from Hasanuddin University 0.29 and Halu Oleo University 0.91. These results show a positive meaning that there is a substantial relationship between the alt value metrics with citation rate of the scientific papers of Hasanuddin University and Halu Oleo University, in addition to showing the scientific paper of Hasanuddin University and Halu Oleo University, besides being popular on academic platforms or international journals (Scopus), they are also popular on social media platforms Twitter, Facebook, Blog, and Mendeley.